Formation of digital competencies among students of economic specialties (Educational Dimension, 2022)
The rapid advancement of digital technology is altering the skillsets required of specialists. In today’s world, a competitive analyst working in the field of economics must possess not only professional skills, but also digital competence, which encompasses not only digital skills, but also a body of knowledge and perspectives on the nature and role of information technologies and opportunities, as well as relevant legal and ethical principles. The article examines modern theoretical foundations and approaches to the development of digital literacy in lifelong learning processes: specifically, one of the tools for determining the level of formation of digital competence using the Tsifrogram test (which is based on the conceptual model of digital competence of citizens DigComp - The Digital Competence Framework for Citizens) is described and analyzed in depth. The study was conducted using competence-based, personality-activity, and communication techniques. The economic analyst training program featured active and interactive teaching methods and practices. The findings of a study on the level of digital competence formation among university students of economic specializations are provided. The most important suggestions for improving students’ digital competence are studied, selected, and highlighted. It is proposed to build a roadmap for boosting students’ digital competency during their university studies in the future.
Keywords: digital competence; DigComp; onstituents of digital competence; self-diagnosis test; digital profile results